Vertical export of marine pelagic protists in an ice-free high-Arctic fjord (Adventfjorden, West Spitsbergen) throughout 2011-2012 - Marquardt, Miriam; Skogseth, Ragnheid; Wiedmann, Ingrid; Vader, Anna; Reigstad, Marit; Cottier, Finlo Robert; Gabrielsen, Tove M. (Aquatic Microbial Ecology, 2019)
The ecosystem role of Arctic microbial communities is still largely unknown. Based on a time-series study at the IsA station (West Spitsbergen), the seasonality and contribution of pelagic protists to the vertical flux was investigated at 7 time points during 2011-2012. The hydrography of this high-Arctic fjord was evaluated to identify impacts on the community composition during the different seasons. Protists (<10 µm and >10 µm) were sampled at 4 depths from the water column and from short-time sediment traps, and investigated by 454 next-generation sequencing of the V4 region of the 18S ribosomal DNA. An advective event during winter, exchanging the cold and less saline water mass with warmer and saline Atlantic Water, was potentially responsible for an abrupt shift in the protist composition in March. Small cells (<10 µm) contributed significantly to the vertical flux during autumn and winter, while larger bloom taxa (e.g. diatoms) predominated the water and traps during spring. Parasitic species, such as MALV 1a and Chytriodinium sp., were also detected in the traps, possibly being transported along with their hosts. Vertical export of Arctic pelagic protists is not limited to the productive period; however, the contribution of small taxa that are important contributors in this study seems to be seasonally influenced and may alter the flux efficiency. Molecular tools revealed new taxa contributing to the vertical export, but also identified new potential mechanisms exemplified by parasite-host-induced transport, spurring increased attention onto parasitism in the study of carbon cycles and vertical flux.